Analysis Of Structure – Conduct - Performance (SCP) on The Merger of State-Owned Enterprise Islamic Banks Based on The Assets Value - Ima Maspupah; Cecep Sudrajat; Jody Mulya Rosid (Sekolah Tinggi Ilmu Bahasa Arab Darul Ulum Banyuanyar Pamekasan, 2022)
Merger is the merging of two or more companies so that the company becomes better and creates new dynamics. Besides that, it creates efficiency and increases market share, expands the business that is run and has stronger competitiveness. This is the goal of the merger of 3 state-owned Islamic banks including BRI Syariah, BNI Syariah and Bank Mandiri Syariah to become Bank Syariah Indonesia (BSI). Bank mergers are deemed necessary in order to create a better bank which in the end can have a significant and positive impact on a banking system that is healthy, efficient, resilient and able to compete in the increasingly tight and competitive global economy and free market. This series of mergers clearly reduced the number of banks. This raises important issues, including whether the smaller number of banks has reduced or even increased the concentration of the banking industry. In addition, it is also interesting to analyze the impact of the merger on the level of banking competition. This study aims to assess the impact of Islamic banking merger policies on market conditions. After the merger, will the market become more competitive or will it become more concentrated? The research method used is literature study. The structure variable is seen from the total assets and market share, the conduct variable is seen through the merger policy. Meanwhile, in analyzing the Performance variable, it is measured through Profit. After analyzing the structure-conduct performance (SCP) by assessing the impact of the sharia banking merger policy, it will be seen that the market is becoming more concentrated or becoming more competitive.